Evolution of the change of direction ability according to the age in school-age children - Rodríguez-Negro, J.; Romaratezabala, E.; Yanci, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The aims of this study were to describe the change of direction ability (CODA) in primary school students (n = 394) and to analyze the differences attending to their age. Significant differences were found in CODA between all courses, except between G1-G2 (p > 0.05, ES = -0.3, small), G1-G3 (p > 0.05, ES = -0.3, small), G2-G3 (p >0.05, ES = 0.1, trivial), G4-G6 (p > 0.05, ES = -0.5, moderate) and G5-G6 (p > 0.05, ES = 0.1, trivial). In the present study no significant differences were observed in the CODA among first, second and third grade students of primary education (6 to 8 years), but significant differences were observed from that age (9 to 12 years). These differences have been especially relevant between G3 and G5. These findings lead us to think that the age of 8-9 years can be a critical differentiating stage in the CODA of the primary education students.